MODERN APPROACHES TO PRESCHOOL EDUCATION SYSTEM IN THE NEW UZBEKISTAN - Norbotayeva Gozal Abdugofurovna (Galaxy International Interdisciplinary Research Journal, 2022)
In our country, preschool education has become an integral part of the continuous education system. The development of this link of education, the formation of the child’s intellectual personality, and the creation of educational services, are paying special attention to improving the quality level, which is the result of consistent reforms in the field. This article talks about the modern approach to the development of preschool education in the new Uzbekistan.